THE DEVELOPMENT OF IKHTILAF AND ITS IMPACT ON MUSLIM COMMUNITY IN CONTEMPORARY MALAYSIA - Man, Saadan (Jurnal Syariah, 2008)
Disagreement (ikhtilaf) on religious issues has been a common phenomenon in Muslim ummah nowadays as a result of their different judgements and perceptions on various matters. In Malaysia, this phenomenon has begun more than a century ago by the advent of Islamic reform movement who strongly denounced most traditional beliefs and practices of Malay Muslims. As a result, there has been a deep conflict between two factions, namely the reformists and the traditionalists, and it remains until present days. This paper aims at analyzing the development of ikhtilaf between these groups since the beginning of 20th until now, as well as its effects on Muslim community in Malaysia. In order to acquire datas regarding this issue, library research and observation are carried out. Among the major findings of this research is that even though ikhtilaf between the reformists and the traditionalists is somewhat crucial, it mainly revolves around furu` issues, and resembles the ikhtilaf of previous ulamas. Even though the conflict mostly resulted in various negative effects, it also, on the other perspective, left some positive consequences on Muslim community in Malaysia.